Seyyed Hossein Nasr's Criticism of Modernist and Orientalist Interpretive Approaches - Mauluddin, Moh; Hariyadi, Muhammad; Arslan, Hamdi (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2025)
In contemporary Qur’anic studies, modernist and orientalist approaches have become increasingly influential. These two approaches offer new frameworks for understanding the Qur’an but often separate the sacred text from its spiritual and metaphysical roots. The modernist perspective emphasizes reason, historical context, and linguistic analysis, while the orientalist view relies on philological and historical-critical methods developed within secular academic traditions. As a result, both tend to reduce the Qur’an to a cultural or historical artifact rather than preserving its role as divine revelation. This study aims to examine the critical perspective of Seyyed Hossein Nasr on these two interpretive trends and to explore the alternative hermeneutical framework he proposes. The research applies a qualitative method using literature review and textual analysis of Nasr’s major writings. The findings reveal that Nasr strongly criticizes both approaches for neglecting the spiritual dimension of the Qur’an. He argues that understanding the Qur’an requires a return to sacred and traditional interpretation methods that emphasize inner spiritual meaning. Nasr promotes a hermeneutic approach that integrates reason, intuition, and spiritual insight, allowing for a more holistic understanding of revelation. He also underscores the role of traditional scholars and spiritual authorities in maintaining the integrity of Qur’anic meaning. The study concludes that Nasr’s alternative framework offers a meaningful response to the limitations of modernist and orientalist interpretations. By restoring the balance between textual analysis and spiritual depth, his approach contributes significantly to enriching Qur’anic hermeneutics. It encourages future scholarship to reengage with the sacred aspects of revelation in ways that are both intellectually rigorous and spiritually grounded. Dalam studi Al-Qur’an kontemporer, pendekatan modernis dan orientalis telah menjadi dua aliran yang semakin berpengaruh. Kedua pendekatan ini menawarkan kerangka baru dalam memahami Al-Qur’an, namun sering kali memisahkan teks suci dari akar spiritual dan metafisiknya. Perspektif modernis menekankan rasionalitas, konteks sejarah, dan analisis linguistik, sementara pendekatan orientalis bergantung pada metode filologis dan historis-kritis yang berkembang dalam tradisi akademik sekuler. Akibatnya, Al-Qur’an cenderung dipandang sebagai artefak budaya atau sejarah, bukan sebagai wahyu ilahi. Penelitian ini bertujuan untuk mengkaji pandangan kritis Seyyed Hossein Nasr terhadap kedua pendekatan tersebut, sekaligus mengeksplorasi kerangka hermeneutika alternatif yang ia tawarkan. Metode penelitian yang digunakan adalah kualitatif, melalui studi pustaka dan analisis teks terhadap karya-karya utama Nasr. Hasil kajian menunjukkan bahwa Nasr secara tegas mengkritik pendekatan modernis dan orientalis karena mengabaikan dimensi spiritual dalam memahami Al-Qur’an. Ia menekankan pentingnya kembali pada metode tafsir yang sakral dan tradisional, yang berfokus pada makna batin dan pengalaman spiritual. Pendekatan yang ia ajukan menggabungkan akal, intuisi, dan wawasan spiritual, serta menekankan peran ulama dan otoritas spiritual dalam menjaga kemurnian makna wahyu. Kesimpulan dari penelitian ini adalah bahwa kerangka alternatif yang ditawarkan Nasr menjadi respon bermakna terhadap keterbatasan penafsiran modernis dan orientalis. Dengan menyeimbangkan analisis teks dan kedalaman spiritual, pendekatan ini memberikan kontribusi penting bagi pengembangan hermeneutika Al-Qur’an, serta mendorong studi-studi masa depan untuk kembali mengaitkan pemahaman wahyu dengan dimensi kesakralan yang mendalam.